Health Disparity Reduction Policy through Community Health Centers in Remote Areas - Andi Hardianti; Asni Hasanuddin; Kamesyworo Kamesyworo; La Ode Asrianto (PT. Anagata Sembagi Education, 2025)
The gap in access and quality of health services in Indonesia, especially in remote areas, is a structural problem that continues to hamper the development of the health sector. The unequal distribution of health workers, limited infrastructure, and low investment in basic service facilities cause people in 3T (Disadvantaged, Frontier, and Outermost) areas to experience delays in medical treatment and high maternal and infant mortality rates. Community health centers as primary health care institutions play a strategic role in overcoming this problem. However, the effectiveness of the role of Community Health Centers is often hampered by the imbalance between central policy design and local conditions, as well as a lack of resources and infrastructure. This study uses a qualitative approach with a case study in one of the 3T areas to explore the challenges and strategies for reducing health disparities through Community Health Centers. The results show that the health policies implemented are often not contextual to local needs, such as limited medical personnel and infrastructure. Therefore, an approach based on local data and involving the community in policy formulation is needed to create more adaptive solutions. Decentralization of policies and the use of technology such as telemedicine are key to increasing the effectiveness of health services in remote areas.